SOME ISSUES OF IMPROVING THE LEVEL OF INTERNATIONAL MARKETING IN FOREIGN ECONOMIC ACTIVITIES OF ENTERPRISES (World Economics and Finance Bulletin, 2022)
The article discusses the main directions of the marketing activity of the enterprise based on the research of various authors. The main factors that modern enterprises in the competitive struggle should focus on in the process of functioning of the enterprise were identified. It was concluded that the main indicators of the effectiveness of marketing activities are quantitative and qualitative indicators that should be followed by marketers of enterprises to improve the efficiency of the functioning of the company.
Keywords: Marketing activity; competition; criteria; estimates